Analisis Penyerapan Tenaga Kerja pada Sektor Usaha Mikro Kecil dan Menengah (UMKM) di Kabupaten Sleman - Wangge, Yohanes Breksmans Raja; Anggrismono, Anggrismono (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of this research is to analyze how much influence business units, domestic investment, foreign investment and regional minimum wages have on labor absorption in the micro, small and medium enterprises sector from 2016 - 2021. The research method used in this research is a quantitative descriptive method using time series data. The data collected in this research uses secondary data obtained from various sources. The research results show that the number of business units, domestic investment, foreign investment, and regional minimum wages have a significant and positive effect on labor absorption in the micro, small and medium enterprises sector in Sleman. Apart from that, based on the research results, it can be concluded that the role of micro, small and medium enterprises in labor absorption is very large, because it can be seen from the development of micro, small and medium enterprises which continues to experience a significant increase, which is proportional to labor absorption in the micro, small and medium enterprises sector.